ASTER-DEM Derived Flood Inundation Map Using 1D-2D Flood Modeller Pro in Kuantan River Basin - Ng, Zone Fhong; Akbari, Abolghasem (ICONTES, 2016)
A topography dataset in the form of digital elevation model (DEM) is require to derive flood prone areas. However, there are different types of DEM for flood inundation mapping. Besides this, flood is one of the most destructive natural hazard which frequently occur in Malaysia. Flood is the cause for loss of life and damage to the people properties and urban infer structures. To mitigate to damages, it would be useful to generate flood extent map as a guideline for local authorities mainly for urban development and flood mitigation purpose. It is always difficult to find elevation dataset in many places. In addition the accuracy of Flood inundation is highly depend on the source of elevation data. There are several source of global free elevation data which can be used for flood modeling. Many research have shown the performance of public domain free available DEM in different countries. However, research on this issue in flat urban river basin in Malaysia is still rare. This research aim to investigate the suitability of Advanced Space Borne Thermal Emission and Reflection Radiometer Global Digital Elevation Model (ASTER-GDEM) for 1D/2D flood inundation modeling in Kuantan river basin. The methodology is based on the integration of ASTER-GDEM and Flood Modeller Pro (FMP) to delineate flood inundation area in Kuantan River Basin (KRB). The river cross sections are generated from ASTER-DEM. The result is shown as a flood effected areas according to time based. Dynamic changes of in flood effected area can be categorized into stages like highest risk, high risk, moderate risk, and low risk for clear visualization by reclassification method. Based on the map, the urban area was prone to the highest risk zone due to the location near to the main river. There are also some areas under highest risk zone. The obtained result conclude that a 30m resolution ASTER-DEM can serve as an input to detailed 2D hydrodynamic modeling in data scarce regions. In this study, the 1D channel model and 2D floodplain model is well presented by using FMP. Flood inundation map is beneficial and important to all local authorities on flood management purpose and urbanization used such as building construction. A good maintenance can be conducted based on the result produced so that the risk of damage will be decrease. According to results obtained, ASTER-GDEM can be used as one alternative for flood inundation map. However it seems ASTER-GDEM does not provide good enough details in flat urban areas.